Creative methods to analyze listed companies on Finnish and American investing-focused message boards - Gråsten, Tiia Anniina (2024)
This research investigated how investors and other stakeholders on the Internet’s investor-focused message boards analyze and comment on listed companies and how accounting information is reflected in these conversations. Research material included message board conversations of eight companies listed in Nasdaq Helsinki and eight listed in the New York Stock Exchange or US Nasdaq. All of the companies operate in the consumer goods and services sector. The conversations were analyzed from three popular investing-focused internet message board services in Finland and the USA. The research material was analyzed by using qualitative and quantitative research methods. For a conclusion, accounting information appeared in conversations frequently and felt important for the users. The most frequently discussed or mentioned accounting topics on the message boards were key financial figures and information such as revenue and operating profit. In addition to traditional accounting information, nonfinancial information felt at least as important and popular as financial information. The most popular nonfinancial information topics were sector development, brand, and message board users' experiences of products and services. There were also minimal differences in how Finnish and American message board users emphasized certain topics. For example, the overall impression was that nonfinancial information was slightly more important for American message board users than Finnish users.